Relationship between Emotional Intelligence and Decision Making Styles And their effect on Performance Excellence the university" An exploratory search for a sample of the administrative leaderships in the Mustansiriya University" - طه, عبد الرحمن مصطفى; عبد الرحمن, وردة عبد الخالق (Journal of Economics and Administrative Sciences, 2014)
Addressed this research the impact of intelligence emotional dimensions of the main(self awareness, and self-management, and social awareness, and relationship management) in the performance excellence the university(performance optimization, and strategic development) this is by middling the styles decision making which are (rational and intuitive, and dependent, and spontaneous, and avoidant), and Go search of an intellectual dilemma raise fundamental questions revolve around the search was to answer those questions through a theoretical framework for search variables first and test models of the relationship and second through the impact six hypotheses President.The objective of the research to make sure the contribution of intelligence emotional in achieving performance excellence the university the middling of decision making styles and that helps the research sample to improve their performance and enhance the level of intelligence emotional to make the right decisions, and applied research on a sample(130) individuals dean and associate dean and head department in(12)College of the Presidency Mustansiriya University,was relying in the questionnaire as an essential tool for the collection of data and information that has been analyzed through the use of a number of statistical methods, the research found, among other conclusions of the most important of which was able to intelligence emotional among a sample search to contribute to bring about more positive changes in the performance excellence the university and seems more in after the performance optimization which is getting where if you are over the decision making styles, and recommends research in benefit sample surveyed by increasing the contribution of emotional intelligence to make a lot of positive effects in the performance excellence the university where the sample need more efforts to improve its performance through the decision making styles and activate the change in the field of strategic development.